Metallic nanoparticles synthesized by marine microorganisms and its application against pathogenic microorganisms: Challenges and opportunities in marine nanotechnology - Vithória Carolyna Trindade dos Santos; Luís Fernando Cusioli; Leticia Nishi; Cristiane Angélica Ottoni; Rosângela Bergamasco (Desalination and Water Treatment)
The supply of drinking water to meet human needs is a major challenge of the 21st century. The public water supply when not treated properly can become the focus of the action of various pathogens. In this context, this work addresses an exploratory and integrative literature review seeking articles that addressed the metal nanoparticles synthesized by marine microorganisms for antimicrobial application in water treatment. The search for articles was conducted using the following search engines: Scielo, Google Scholar, Portal Capes, Springer, Scopus® and Reed Elsevier. The search terms ''water treatment'', ''biological synthesis of metal nanoparticles'', ''marine microorganisms'' were used as keywords. Metal nanoparticles have emerged as a technological innovation due to their enhanced physical and chemical properties and antimicrobial characteristics. Different synthesis methods are widely described in the literature, however, the biological synthesis is a promising alternative to those obtained synthetically, since they do not generate waste and present less toxicity. Bacteria, fungi and plants are the main organisms described as producers of nanoparticles. With the increasing search for new metabolites, microorganisms have been increasingly studied for industrial applications. Among these utilized microorganisms, isolates from marine environments have received global attention, as they are able to survive in an extreme environment exhibiting a differentiated metabolic diversity. This study reported that metal nanoparticles synthesized by microorganisms present a biological coating that increases their biocompatibility, making the material less toxic and maintaining its antimicrobial characteristics. The data suggest that marine microorganisms have shown themselves as promising nanofactories of metallic nanoparticles with the potential to provide water quality from a low-cost and ecofriendly process, and that there is an increasing need to explore and develop alternative and viable methodologies for water treatment.